Power recovery of the PV arrays under partial shading by a power electronic compensator. (1st May 2022) - Torkian, Farzad; Ghandehari, Reza
Abstract: The partial shading phenomenon in some modules of the PV arrays limits the total current of the series modules and reduces the total output power. In this paper, a power electronic compensator with a multi-winding transformer is presented to recover the undelivered energy of the shaded modules. The proposed configuration compensates reduced currents due to the partial shading on the series modules by injecting the required currents into parallel circuits of the shaded modules. The unshaded modules provide the compensatory currents by creating a common flux into the core of the multi-winding transformer. The average current and the output power of the PV array are considerably improved under partial shading conditions. The proposed configuration has a very simple and sensorless control structure, and its power electronic elements are less than other improving configurations. The simulation and experimental results confirm the presented analytical relations and desirable performance of the proposed configuration to recover the undelivered energy of the PV array under the partial shading conditions. Highlights: The proposed configuration recovers the undelivered energies of the shaded modules. The presented compensator has a very simple and sensorless control structure. The method can enhance the PV output power under all shading patterns. Energy recovery is considerable than the fixed and dynamic reconfiguration methods.